Unraveling the Structure Transition and Peroxidase Mimic Activity of Copper Sites over Atomically Dispersed Copper‐Doped Carbonized Polymer Dots. (12th January 2023) - Gao, Fucheng; Huang, Jian; Ruan, Ying; Li, Hui; Gong, Pengyu; Wang, Fenglong; Tang, Qunwei; Jiang, Yanyan
Abstract: The lack of systematic structural resolution makes it difficult to build specific transition‐metal‐atom‐doped carbonized polymer dots (TMA‐doped CPDs). Herein, the structure‐activity relationship between Cu atoms and CPDs was evaluated by studying the peroxidase‐like properties of Glu−Cu−CPDs prepared by using copper glutamate (Glu) with a Cu−N2 O2 initial structure. The results showed that the Cu atoms bound to Glu−Cu−CPDs in the form of Cu−N2 C2, indicating that Cu−O bonds changed into Cu−C bonds under hydrothermal conditions. This phenomenon was also observed in other copper‐doped CPDs. Moreover, the carboxyl and amino groups content decreased after copper‐atom doping. Theoretical calculations revealed a dual‐site catalytic mechanism for catalyzing H2 O2 . The detection of intracellular H2 O2 suggested their application prospects. Our study provides an in‐depth understanding of the formation and catalytic mechanism of TMA‐doped‐CPDs, allowing for the generation specific TMA‐doped‐CPDs. Abstract : Atomically dispersed copper‐doped carbonized polymer dots (CPDs), Glu−Cu−CPDs, with excellent peroxidase‐like activity were prepared from copper glutamate (Glu). The Cu binding sites in Glu−Cu−CPDs had a Cu−N2 C2 structure, and Cu−O bonds were converted into Cu−C bonds under hydrothermal conditions. DFT calculations showed that H2 O2 was cleaved by Glu−Cu−CPDs by a dual‐site catalytic pathway. The Glu−Cu−CPDs enabled intracellular detection of H2 O2 .